The effects of globalization on the women's press - Orsini, Marta (2015)
When academic works analyze the consequences of Globalization or other deep transformations that marked the world in the last decades of the 20th century, they usually treat them from the viewpoint of the groups that are socially dominant in the public spheres of power. Thus, women – historically marked by abuse and discrimination in all senses – become invisible stakeholders in the majority of academic researches. In this article, we emphasize the case of women's magazines, a frequently undervalued sector despite its enormous economic relevance and its influence on media in general. We address the historical context that made women's magazine cross the borders of their countries of origin in the past few decades and strengthen their role as protagonists in the general media. Furthermore, we will analyze how a few national women's magazines from Brazil, Mexico, Portugal and Spain relate to feminism. This way, we intend to make visible the transcendence that the only media sector specifically aimed at women has.